2018
DOI: 10.1007/s12551-018-0446-z
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning and feature selection for drug response prediction in precision oncology applications

Abstract: In-depth modeling of the complex interplay among multiple omics data measured from cancer cell lines or patient tumors is providing new opportunities toward identification of tailored therapies for individual cancer patients. Supervised machine learning algorithms are increasingly being applied to the omics profiles as they enable integrative analyses among the high-dimensional data sets, as well as personalized predictions of therapy responses using multi-omics panels of response-predictive biomarkers identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
119
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(121 citation statements)
references
References 70 publications
1
119
0
1
Order By: Relevance
“…Quantitative Structure-Activity Relationship (QSAR) models establish a mathematical relationship between the chemical structure of a molecule, encoded as a 3 set of structural and/or physico-chemical features (descriptors), and its biological activity on a target. Such methods have been successfully used in a wide variety of pharmacology and drug design projects 13 , including cancer research [14][15][16] . QSAR models are traditionally built using simple linear models [17][18][19][20] to predict the activity of individual molecules against a molecular target.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative Structure-Activity Relationship (QSAR) models establish a mathematical relationship between the chemical structure of a molecule, encoded as a 3 set of structural and/or physico-chemical features (descriptors), and its biological activity on a target. Such methods have been successfully used in a wide variety of pharmacology and drug design projects 13 , including cancer research [14][15][16] . QSAR models are traditionally built using simple linear models [17][18][19][20] to predict the activity of individual molecules against a molecular target.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth pointing out that they used a form that is more general than Eqn. (9) so that the responses data do not necessarily involve the same set of cell lines for different drugs.…”
Section: Bayesian Inference Methodsmentioning
confidence: 99%
“…An approach to compensate for the lack of genetic hotspots in NF1 tumors is to focus on combinations of transcriptomic signatures that may be unique to specific tumor types. In other tumor types, transcriptomic landscapes across cancer datasets [18,19] have shown that combining RNA-seq data from similar diseases can identify expression profiles that correlate with prognosis [20] , predict drug response [21,22] or identify key tumor biology [23] .…”
Section: Introductionmentioning
confidence: 99%